Relaksasi Otot Progresif terhadap Penurunan Tekanan Darah pada Pasien Hipertensi - Alya Farah; Heny Siswanti; Tri Suwarto (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Hypertension is a non-communicable disease known as the silent killer because it is often asymptomatic but may lead to cardiovascular, cerebrovascular, renal, and vascular complications. This study aimed to analyze the effect of progressive muscle relaxation therapy on blood pressure reduction among hypertensive patients in the Anggrek Ward of Prima Medika Hospital, Pemalang. A quasi-experimental pretest–posttest control group design was employed. A total of 66 participants were selected using purposive sampling and assigned to intervention and control groups. Data were collected using a digital sphygmomanometer, respondent characteristic forms, and observation sheets, then analyzed using the Wilcoxon and Mann–Whitney tests. The intervention group demonstrated a significant reduction in blood pressure (p = 0.000), whereas no significant change was observed in the control group (p = 0.366). The Mann–Whitney test also indicated a significant difference between groups (p = 0.000). Progressive muscle relaxation is an effective complementary therapy for reducing blood pressure in patients with hypertension.